2008
DOI: 10.1021/jp809662a
|View full text |Cite
|
Sign up to set email alerts
|

Immobilization of BSA on Silica-Coated Magnetic Iron Oxide Nanoparticle

Abstract: Colloid stable magnetic iron oxide nanoparticles, which undergo reversible precipitation from aqueous solution with external magnetic flux, can have many potential applications. However, the lack of generic homogeneous anchoring sites on a magnetic nanoparticle surface for binding of chemical/biochemical species under a wide range of conditions is one key problem. It is shown that a small size iron oxide nanoparticle encapsulated in a thin silica shell can offer specific sites to bind protein molecules via sur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
73
1

Year Published

2011
2011
2018
2018

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 103 publications
(79 citation statements)
references
References 24 publications
5
73
1
Order By: Relevance
“…Superparamagnetic iron oxide nanoparticles (SPIONs), including magnetite (Fe 3 O 4 ) and maghemite (γ-Fe 2 O 3 ), have been extensively utilized in biomedical applications, including as magnetic resonance imaging contrast agents, 1 for biocatalysis, 2 for biological separation, 3 for biosensing, 4 diagnostic medical devices, 5 and hyperthermia. Among these applications, hyperthermia 6 is a physical therapy in which SPIONs generate heat and thus kill cancer cells when they are exposed to an external magnetic field.…”
Section: Introductionmentioning
confidence: 99%
“…Superparamagnetic iron oxide nanoparticles (SPIONs), including magnetite (Fe 3 O 4 ) and maghemite (γ-Fe 2 O 3 ), have been extensively utilized in biomedical applications, including as magnetic resonance imaging contrast agents, 1 for biocatalysis, 2 for biological separation, 3 for biosensing, 4 diagnostic medical devices, 5 and hyperthermia. Among these applications, hyperthermia 6 is a physical therapy in which SPIONs generate heat and thus kill cancer cells when they are exposed to an external magnetic field.…”
Section: Introductionmentioning
confidence: 99%
“…[24,25] The intensities of the RR band at 1338 cm −1 with different dilutions of FBS are shown in Fig. 6.…”
Section: Resultsmentioning
confidence: 99%
“…Due to their high affinities for hydrophobic surfaces, adsorbed proteins can have a less native structure than when adsorbed on hydrophilic surfaces, leading to severe protein denaturation 67 . In addition, NP surfaces may take up proteins depending on their isoelectric points in a rather narrow pH range 68 . It has also been observed that an increase in electrostatic interaction is generally accompanied by a reduction of the modification of the native structure 69 .…”
Section:  Effects Of Hydrophobicity/hydrophilicitymentioning
confidence: 99%